A study on the perception of moonlighting practices among the employees of public hospitals in Klang Valley / Mohd Zdikri Md Sabron and Aliza Abu Hassim - Md Sabron, Mohd Zdikri; Abu Hassim, Aliza (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Moonlighting is considered as dual career or multiple jobs carried out by employees. It was reported that, public officials had a high rates employee's engaging in moonlighting. But the fact is how public officials accurately managing their interest of need then give full commitment to their primary job. This study examines to seek to understand employees' perception on moonlighting practices. The types of investigation in this paper is causal study whereby this study is conducted in order to determine the important factors that associate with the moonlighting practise among employees. Self-questionnaires were distributed to respondent in the process to get important view towards this moonlighting activity. This study was conducted among 375 respondents from four public Hospitals which include Hospital Kuala Lumpur, Hospital Ampang, Hospital Tuanku Ampuan Rahimah and Hospital Putrajaya. This study also adopts and adapt from Bandura (1997) concept which is Social Cognitive Theory, (Environment factors, personal factors and behavior factors). In addition, basic statistical and advance analytical tools have been employed to evaluate the findings. This study used analytical process includes factor analysis, correlations regression analysis and Hayes model process for moderator effect. From the findings obtained, environment factor and personal factor had a positive relationship and significant towards employees' engagement in moonlighting. The result shows environmental factors and personal factor influence employees' engagement in moonlighting. However, behaviour factor is not significant towards employees' engagement in moonlighting. At the end of this study, conclusion and recommendation made based on the result of the findings.